A THREE-LEVEL MODEL OF MEDIA MONITORING SYSTEMS IN THE LANDSCAPE OF MODERN TECHNOLOGIES: INFRASTRUCTURAL, ANALYTICAL AND STRATEGIC APPROACHES (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis analyzes the role of media monitoring systems in the ecosystem of modern technologies on the basis of a systematic approach. In the context of digital transformation, the increasing volume, speed and complexity of information flows are turning media monitoring programs from a simple control tool into a strategic management instrument. The study substantiates a three-level model of monitoring systems: data collection infrastructure, analytical layer and strategic management level.
Keywords: Media monitoring programs, communication, data collection infrastructure, analytical layer, natural language processing (NLP), sentiment analysis, machine learning, trend detection, reputational risk, data-driven management, communication KPI, information security, media intelligence, strategic communication.